Potential of Cash Waqf as Financing for MSMEs in Medan City - Sabaruddin Chaniago; Yogi Putra; M. Indra Mulia Nasution (Enrichment : Journal of Management, 2021)
This study aims to determine the role of cash waqf in empowering MSME actors in Medan City. The results of the study stated that the problem in implementing the Potential of Cash Waqf as the Empowerment of MSMEs in Medan City includes two important components, namely: internal and external. aspects of internal problems include two important aspects, namely: human resources and accountability issues. Meanwhile, the external problem lies in 2 aspects, namely: the problem of authority, the problem of society in general. Thus, things that become important in implementing the potential of cash waqf as an empowerment of MSMEs in Medan City from the authority side: 1) supervision issues, 2) nazhir certification 3) Violation penalties for nazhir who do not carry out their duties properly. Meanwhile, in terms of the general public, it consists of a priority order: 1) trust (public trust) which is still relatively low 2) Minimal education, 3) Lack of public awareness of cash waqf 4) guarantees provided by cash waqf managers for cash waqf .